Dentition status and treatment needs of engineering students in Lucknow city - Mayank Agrawal; Sonam Agrawal; P Anuradha; Smita D Dutta; Arpit Sharma; Mukesh Gupta; Sarita Chopra (Wolters Kluwer Medknow Publications, 2014)
Introduction: Professional college students should be more aware of their health. The simple concept of oral hygiene should be understood and put into practice by them. Objectives: To assess the dentition status and treatment needs of engineering students in Lucknow city. Materials and Methods: A total of 500 subjects were included in the study. The subjects were selected from four Engineering colleges randomly selected from all parts of the city. Data were collected by using oral health assessment form by WHO (1997). The proforma included questions on oral hygiene practices, dentition status and treatment needs. Statistical analysis was performed using Statistical Package for Social Sciences version 15.0. Results: Among the total subjects, 56% of the subjects were males and 44% were females in the study. Decayed teeth were found among 52.8% of the subjects in the present study. However, frequency of filled teeth (4%), missing (4.8%), bridge abutment (0.4%) and trauma (5.2%) was small. One surface filling was required among 26.4% of the subjects, 2 or more surface filling was required among 8%, crown for 5.2%, pulp care was 6.4% and extraction was required in 4.4% of the subjects. The decayed, missing, and filled teeth score among male subjects was 1.02 ± 1.20 and females 0.82 ± 0.94. Conclusion: The dental caries among the engineering students was found to be high and were more in males when compared to the females.